Lavender morning - Deveraux, Jude. (New York : Atria Books, 2009)
When Miss Edi passes away, she leaves Jocelyn Minton all her worldly possessions, including an eighteenth-century house and a letter with clues to a mystery that began in 1941. In an attempt to understand the legacy that has been left to her, Jocelyn digs into Miss Edi's mystery and soon discovers some shocking surprises about her family's history and a man with his own mysterious past.
Keywords: Inheritance and succession -- Fiction; Self-actualization (Psychology) -- Fiction; Love stories